La conciliation travail-famille, dimension fondamentale de la qualité de l’emploi - Olivier Marchand (Revue Interventions Économiques)
This paper situates the issue of Work-Family Reconciliation in the wider context of « quality of employment », which concentrates the attention on the professional aspects of the question.It then addresses in a transversal way the role of the three supranational organizations that are the ILO (International Labour Organisation), the Dublin Foundation and the European Commission in the governance of the issue. First of all the paper addresses the issue of what is meant by « quality of employment » or « decent work », as it is labelled by the ILO ? In the wider sense, it is a multidimensional concept which concerns quality of employment and its content, but also the characteristics of employment and the person who occupies the job, and finally the environment of workers and the functioning of the labour market in general. The paper highlights the diversity of contents and shows that Work-family reconciliation can relate to the macro as well as the meso level.